2000
DOI: 10.1046/j.1365-2281.2000.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between mitral annulus motion and ejection fraction changes with age and heart size

Abstract: Mitral annulus motion (MAM) has recently been introduced as an index of left ventricular function. Several echocardiographic studies have shown good agreement between ejection fraction (EF) and MAM x 5, where MAM is the total mitral annulus motion, measured in mm, and EF is expressed as a percentage. This means that if MAM is used for estimation of left ventricular function, the conversion factor 5 is used, if the function is expressed as EF. In these studies, the mean age of the patients was over 60 years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…AVPD and TDI may be superior in detecting subtle abnormalities of LV systolic function [43] and in patients with subclinical heart disease [44,45], as well as with increasing age [46]; longitudinal contractility is reduced whereas LVEF is preserved. A number of possible mechanisms exist by which subendocardial, longitudinal LV function may become impaired earlier than subepicardial, circumferential LV function [47].…”
Section: Discussionmentioning
confidence: 99%
“…AVPD and TDI may be superior in detecting subtle abnormalities of LV systolic function [43] and in patients with subclinical heart disease [44,45], as well as with increasing age [46]; longitudinal contractility is reduced whereas LVEF is preserved. A number of possible mechanisms exist by which subendocardial, longitudinal LV function may become impaired earlier than subepicardial, circumferential LV function [47].…”
Section: Discussionmentioning
confidence: 99%
“…MAPSE represents a direct measure of the ratio of longitudinal left ventricular wall contractility during systole and diastole, whereas LVEF represents the indirect ratio of LV volumes being assessed by circumferential planimetrics of the LV cavity. Therefore, MAPSE might reveal more subtle and direct contractility dysfunctions compared to LVEF [33]. It was shown that patients with a preserved ejection fraction (those with increasing age, hypertension, myocardial hypertrophy, or diastolic dysfunction) reveal an impaired long-axis contractile function earlier, even when radial function still remains preserved [34].…”
Section: Discussionmentioning
confidence: 99%
“…M-mode images were obtained at the LV septal, lateral, anterior, and posterior borders of the mitral ring in the apical 2C- and 4C views, and an average mitral annular plane systolic excursion (MAPSE) value was calculated [18]. …”
Section: Methodsmentioning
confidence: 99%